Tanpa Sosok Ayah: Dampak Fatherless pada Hubungan Romantis Dewasa Awal - Purwanti, Dewi Asih; Dimala, Cempaka Putrie; Mustika, Haryanti (EduInovasi: Journal of Basic Educational Studies, 2025)
The absence of a father figure in a child’s life has a long-term impact on the psychological and social development of the individual, particularly in forming interpersonal relationships such as romantic relationships in early adulthood. This study aims to determine whether there is an influence of fatherlessness on romantic relationships, with a total of 204 participants, who are young adults who have experienced fatherlessness and are currently in romantic relationships. This study employs a quantitative method with a causal design, non-probability sampling techniques, and accidental sampling as the sampling method. Two scales were used in this study: the Father Presence Questionnaire and the Relatiionship Assesment Scale, with data analysis conducted using simple linear regression techniques. The analysis results indicate a significant influence between fatherlessness and romantic relationships in young adults, with a significance value of 0.000 (p <0.05). The result of this study show that the higher the level of fatherlessness in young adults, the stronger the romantic relatinships that can be built. This indicates a tendency to become closer to one’s partner as an effort to fill the void caused by the absence of a father in the past. The influence shown is quite strong with an R value of 0.674 and R-square of 0.455, meaning that 45,5% is fluence by the fatherless factor while the remaining 54,5% is influenced by other factors. One of the other factors influencing romantic relationships is communication.